Polos de turismo em regiões subdesenvolvidas: estudo de caso do Polo Costa dos Corais, Alagoas - Duda, João Itácito Morais (2013)
This study examines the extent to which the Theory of Growth Poles, once adapted to tourism, is appropriate to underdeveloped regions. Brazil’s tourism poles policy, which is part of the country’s strategy of tourism regionalization, was created based on the Theory of Growth Poles. The policy is implemented through descentralization of tourism planning and management, with states being called to play a central role in the implementation of the policy. This policy was crafted under the assumption that tourism can help the development of poor regions, based on the influence of preexisting dynamic tourist centers, the so-called “Destinos Indutores” (Tourism-Attractor Destinations). To this effect, the federal government encourages the creation of basic infrastructure in the tourism poles in order to attract private investments, the development of public institutions direct and indirectly linked to tourism, economic growth, the creation of jobs, income improvements, and delivery of more urban services in the target regions. However, underdeveloped regions or countries like Brazil tend to face difficulties to deliver such public policies. Factors such as economic e politic instabilities, institutional weaknesses, deficiencies in basic infrastructure and public services, in addition to a lack of interest on the part of officials of public administration bodies, may represent stumbling-blocks to the regionalization of tourism, based on the Theory of Growth Poles. This study encompassed 11 municipalities of the North coastal zone of the Alagoas state which form the Polo de Turismo Costa dos Corais (Costa dos Corais Tourism Pole). So, the study adopted a case study approach whose main data-collection instruments were documental analysis and open interviews with public officials of the Alagoas’s State Secretary of Tourism (Setur-AL). Data were analyzed in a qualitative way. Conclusions indicate that the state of Alagoas has faced difficulties regarding both the planning and implementation of the Polo de Turismo Costa dos Corais due to politico-administrative, economic and socio-cultural problems, based on which the suggestion is advanced here according to which states or regions with similar contextual characteristics may not have all the necessary pre-requisites to effectively plan and implement tourism development poles, at least not of the type that is fomented by Brazil’s Ministry of Tourism.